The infinite desire for growth - Cohen, Daniel, 1953- (2018)
"Leading economist Daniel Cohen provides a whirlwind tour of the history of economic growth, from the early days of civilization to modern times, underscoring what is so unsettling today. The new digital economy is establishing a "zero-cost" production model, inexpensive software is taking over basic tasks, and years of exploiting the natural world have begun to backfire with deadly consequences. Working hard no longer guarantees social inclusion or income. Drawing on economics, anthropology, and psychology, and thinkers ranging from Rousseau to Keynes and Easterlin, Cohen examines how a future less dependent on material gain might be considered and, how, in a culture of competition, individual desires might be better attuned to the greater needs of society."--Publisher's description.